General condition assessment method for signalized intersections: the case of Ibague, Colombia (2024)
This study proposes a new method created to perform a universal assessment on the status of signalized intersections implemented in the city of Ibague, Colombia. The condition of each signalized intersection is classified according to parameters established to improve vehicular and pedestrian traffic, as well as the long-term development of the city. To achieve the research objective, the aspects to be evaluated are divided in two categories: Functionality and Utility, as well as specific criteria for each of them. Therefore, field data is collected using a geospatial tool and assigning levels of importance associated with a numerical scale that is plotted on maps of influence. We can therefore conclude that the proposed assessment method is not only necessary, but suitable for the evaluation of signalized intersections, which effectively assess the pertinent aspects, granting a rating supported by their respective analysis, and making the comparison of their specific conditions over time possible. For example, in the case study of Ibague 2023, according to the evaluation method, 59% of the intersections were ranked in the lowest states of the scale, also showing that between 2018 and 2023 there was an overall decay, as most of the intersections (85%) lowered their ratings and degraded to a greater extent compared to those with improvements.